Analysis of the Utilization of Technology-Based Learning Media in Elementary School Students' Listening Skills: A Systematic Literature Review - Siregar, Sina Wardani; Sunendar, Dadang; Nanola, Nouval; Burhanudin, Burhanudin (Mimbar Sekolah Dasar, 2024)
The ability to convey messages through sounds is known as language skills, with listening skills being one of its most essential components. Listening skills are developed by children before they can speak, read, and write. However, these skills are often neglected, which affects other language skills. To improve students' listening skills, it's necessary to use innovative and creative learning media. Learning media is a teaching strategy employing innovative learning tools to achieve the intended learning objectives. This research aims to provide an in-depth understanding of using technology-based learning media to improve students' listening skills. After analyzing 24 articles using the Systematic Literature Review (SLR) method, the study concludes that technology-based learning media positively influences students' listening abilities. Using technology-based learning media during the learning process enhances students' enthusiasm and interest in learning. Learning media positively influences students' listening abilities. Using technology-based learning media during the learning process enhances students' enthusiasm and interest in learning. The analysis results indicate that using technology-based learning media, such as podcasts, animated videos, and audiovisual materials, has a positive impact on students' listening skills. The observable outcomes include increased student interactivity and improved understanding of a broader and deeper context regarding information.